2019
DOI: 10.1002/pros.23837
|View full text |Cite
|
Sign up to set email alerts
|

The metastasis suppressor CD82/KAI1 represses the TGF‐β1 and Wnt signalings inducing epithelial‐to‐mesenchymal transition linked to invasiveness of prostate cancer cells

Abstract: Background The epithelial‐to‐mesenchymal transition (EMT) is closely associated with cancer invasion and metastasis. Since the transforming growth factor β (TGF‐β) and Wnt signals induce EMT in various epithelial cell types, we examined whether and how the CD82/KAI1 metastasis suppressor affects the TGF‐β and Wnt signal‐dependent EMT in human prostate cancer cells. Methods The invasiveness of cancer cells was evaluated by examining their ability to pass through the basement membrane matrigel. The subcellular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 52 publications
(158 reference statements)
0
19
1
1
Order By: Relevance
“…A number of recent studies have reported on the progression of PCa and EMT in TGF-β1 regulating PCa cells (43)(44)(45)(46). However, in the present study, we found that the auto-regulatory axis miR-20b-5p/TGFBR2/E2F1, which is regulated by TGF-β1, is involved in PCa development and progression through regulating EMTrelated gene expression.…”
Section: Discussioncontrasting
confidence: 72%
“…A number of recent studies have reported on the progression of PCa and EMT in TGF-β1 regulating PCa cells (43)(44)(45)(46). However, in the present study, we found that the auto-regulatory axis miR-20b-5p/TGFBR2/E2F1, which is regulated by TGF-β1, is involved in PCa development and progression through regulating EMTrelated gene expression.…”
Section: Discussioncontrasting
confidence: 72%
“…Also, the genes that regulate cell proliferation, survival, and metabolism (e.g., Cyclin D1 and Myb ) are strongly affected [ 127 ]. Additionally, expression of the genes involved in regulation of the stability of E-cadherin/β-catenin complexes appeared suppressed, strengthening the intrinsic role of CD151 in cell-cell adhesion [ 34 , 116 , 117 , 137 ]. In contrast, CD151 disruption markedly blunts survival of epithelial basal cell-derived tumor cells [ 28 ], consistent with the impact of CD151 knockdown on MDA-MB-231 cells [ 38 , 71 ].…”
Section: Molecular Basis For Functional and Signaling Versatility Of Cd151 And Other Tetraspaninsmentioning
confidence: 99%
“…Intriguingly, there is growing evidence that many tetraspanins such as CD151 and CD82 can negatively or positively influence tumor development and metastasis in oncogenic context- and cell lineage-dependent manners, where they regulate strength of cell-cell junctions, signal transduction of the Wnt pathway, the epithelial-mesenchymal transition (EMT), maintenance of cancer stem cells (CSCs), and dynamics of exosomes ( Table 1 ) [ 20 , 21 , 28 , 33 , 34 , 35 ]. This emerging paradigm presents a challenge to conceptualize functional and signaling roles of the tetraspanin family in human cancer, and their utilities as biomarkers and drug targets for cancer diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-c can induce epithelial-tomesenchymal transition (EMT) in PCa cells via the JAK-STAT signaling pathway [75], and STAT3 may directly mediate EMT progression and regulate ZEB1 expression in CRC [76] PCa progression, cell proliferation, and inhibition of apoptosis [51,52] No direct analysis of these pathways in CTCs Wnt/ β-catenin Dysregulation of Wnt/β-catenin signaling has been implicated in the development of cancer in different tissues such as lung, skin, liver, and prostate [52], via regulating Zeb1 in CRC [77] Wnt/β-catenin pathway promotes the metastatic spread of prostate cancer cells by inducing EMT [78] Epithelial type CTCs and activation of Wnt/β-catenin signaling in lung cancer cells [79]. No report in PCa CTCs Notch Crosstalk between the Jagged1/Notch and JAK/STAT3 signaling pathways by promoting EMT through Jagged-1 in ovarian cancer [80] Notch signaling results in prostate tumor recurrence via EMT [81] Increased production of ROS results in the upregulation of Notch1 in CTCs in metastatic breast and melanoma cancer [82].…”
Section: Jak/ Statmentioning
confidence: 99%